Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of copper content of boric acid, boric oxide and $7Idi$7Rsodium tetraborates Part 7, (28th February 1979) - British Standards Institution,
No abstract available